Effects of crude palm oil as plasticizer in polyoefin blown film - Jusoh @ Taib, Emiliana Rose (2011)
The growing of public concern about environmental and health potential risks of polymer and plasticizer industry promises to increase the market for an alternative of safer plasticizer such as a vegetable oil based plasticizer. The purpose of this study was to investigate the effect of crude palm oil (CPO) as plasticizer in polyolefins blown film. The two types of polyolefins ; low density polyethylene (LDPE) and polypropylene (PP) were blended with 1%, 3%, 5% of CPO using a twin screw extruder. The extruded samples were blown using the blown thin film technique. Mechanical, thermal, physical and morphological properties were characterized. The addition of CPO into low density polyethylene (LDPE) enhanced the elongation at break about 79 to 90% in machine direction (MD) and transverse direction (TD) and gradually decreased the tensile strength about 9%. The rupture properties (impact and tear strength) of LDPE modified with CPO showed the decrement pattern due to the plastisticization effect. The polypropylene (PP) modified with CPO results presented a good mechanical properties results on tensile strength (increased about 17% in TD and decreased about 17% in MD), elongation at break (enhanced about 30-90% in MD and decreased about 40-50% in TD), increased the impact strength and tear strength. The scanning electron microscopy photographs of LDPE and PP modified CPO did not modify the basic fracture mechanism of LDPE and PP matrix. The presence of CPO in LDPE and PP matrices were decreased the density and increased the melt flow rate. From Fourier Transmission Infra-Red (FTIR) spectras,the presence of CPO showed the addition peak in 1745 to 1747 cm-1 region indicated the physical molecular interaction between polyolefins and CPO. The thermogravimetric analysis (TGA) results showed that incorporation of CPO as plasticizer showed small increased effect in the thermal stability for both polyolefins. From the dynamic mechanical analysis, the storage modulus and loss modulus for both polyolefins presented decreasing pattern due to the action of CPO as plasticizer which introduced free volume and enabled the polyolefins chains to deform more easily. The glass transition temperatures (Tg) of both polyolefins determined from the peak of tan δ and were shifted to lower temperature with the increasing CPO content. This observation showed that the CPO reacted as plasticizer in polyolefins system. The plasticising effect of CPO in polyolefins was investigated and proved that the plasicization mechanism occurred in the polyolefins systems. These findingshave contributed new knowledge to the additives area and give important implications for designing and manufacturing polymer packaging materials.